A qualitative study on coping strategies among women from food insecurity households in Selangor and Negeri Sembilan - Sulaiman, Norhasmah; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir; Kandiah, Mirnalini; Abu Samah, Asnarulkhadi (Nutrition Society of Malaysia, 2010)
Understanding the experiences of household food insecurity is essential for better measurement and assessment of its nutritional, physical and psychological consequences. This qualitative study explored coping strategies and their perceived severity in relation to household food insecurity. Women (n=57; 20-50 years old) from rural and urban areas in Selangor and Negeri Sembilan participated in this study. These women were interviewed using a semi-structured questionnaire. The questionnaire was divided into two parts, that is, demographic and socio-economic information and women's experiences of coping with household food insecurity. Women were chosen since they were primarily responsible for food acquisition and preparation for the all household members. Thematic analysis was utilized in data analysis. Thematic analysis is a method for identifying, analysing and reporting patterns and themes of the qualitative data. Themes capture something important related to the study objectives and describe an integrating as well as relational idea from the data. Results showed that households displayed a variety of non-food related coping strategies and food-related coping strategies. Women's descriptions of non-food related coping strategies to food insecurity were categorised into five themes i.e. cloth purchasing behaviors, reduce school-going children's expenditure, delay the payment of bills, adjust lifestyle and increase cash and income earning. Food related coping strategies were categorised into four themes i.e. food stretching, food rationing, food seeking and food anxiety. Food stretching is a strategy of food insecurity that affects the quality of diet. Food rationing comprises coping strategies of food insecurity related to the quantity of food available for household's consumption. Food seeking is a strategy of acquiring food through socially unacceptable ways and food anxiety is a strategy that indicates households allocating money to buy staple food in order to prevent food insecurity. Each coping strategy showed a different level of perceived severity, that is, less severe, quite severe, severe and very severe. In conclusion, the qualitative data provide valuable information for understanding the experiences of food insecurity that can be used as a basis to develop direct indicators that can capture the core behaviours and their level of severity to measure household food insecurity.